Weak law week conversation - T. Smith (Law Text Culture, 1995)
In Law Week 1992, a NSW Court ruled that the old Education Department building known as the Bridge Street HQ, was not available for claim by local Aborigines. Legislation gives the Aborigines the right to press land claims on unoccupied crown land, and the Greiner Government had moved the Department from the building, planning to convert it to a casino. The court's ruling was based on the fact that the Government had left a skeleton staff there for the specific purpose